2018
DOI: 10.1016/j.biomaterials.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically cartilage-mimicking poly(PCL-PTHF urethane)/collagen nanofibers induce chondrogenesis by blocking NF–kappa B signaling pathway

Abstract: Cartilage cannot self-repair and thus regeneration is a promising approach to its repair. Here we developed new electrospun nanofibers, made of poly (ε-caprolactone)/polytetrahydrofuran (PCL-PTHF urethane) and collagen I from calf skin (termed PC), to trigger the chondrogenic differentiation of mesenchymal stem cells (MSCs) and the cartilage regeneration in vivo. We found that the PC nanofibers had a modulus (4.3 Mpa) lower than the PCL-PTHF urethane nanofibers without collagen I from calf skin (termed P) (6.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…The authors therefore speculated that, in the presence of the scaffolds, MSCs behaved as if they were exposed to an external inflammatory stimulus. Similar results have been recently reported for MSCs cultured on electrospun fibers of PCL/polytetrahydrofuran (PTHF) urethane (P fibers) and PCL-PTHF urethane/collagen I (PC fibers) (Jiang et al, 2018 ). In this case, down-regulation of genes that contribute to inflammation and suppression of the NF-kB pathway signaling pathway were achieved by changing the mechanical properties of the fibers.…”
Section: Effects Of Fiber Topography and Micro-patterning On Cellularsupporting
confidence: 87%
“…The authors therefore speculated that, in the presence of the scaffolds, MSCs behaved as if they were exposed to an external inflammatory stimulus. Similar results have been recently reported for MSCs cultured on electrospun fibers of PCL/polytetrahydrofuran (PTHF) urethane (P fibers) and PCL-PTHF urethane/collagen I (PC fibers) (Jiang et al, 2018 ). In this case, down-regulation of genes that contribute to inflammation and suppression of the NF-kB pathway signaling pathway were achieved by changing the mechanical properties of the fibers.…”
Section: Effects Of Fiber Topography and Micro-patterning On Cellularsupporting
confidence: 87%
“…Total RNA was isolated from chondrocytes using an RNA isolation kit (Margen, China) and the qRT-PCR was performed according to the study previously reported [ 42 ]. The primer sequences used for qRT-PCR were presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The animal study was approved by the Committee on the Ethics of Animal Experiments of Guangxi Medical University (2017‐02‐03). The animal experiment conditions were as previously stated (animal experimental statement) . Ten‐week‐old male SD rats were anesthetized using 2.5% sodium pentobarbital (30 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have recently attracted much attention as sources for the clinical therapy of a variety of diseases , including cartilage injury, due to their ease of expansion and wide range of functions . Recruited MSCs can be specifically induced along the chondrogenic lineage in the presence of specific growth factors, molecules, and epigenetic modifications.…”
Section: Introductionmentioning
confidence: 99%